Gerakan Budaya Menjelang Kemerdekaan Indonesia-Malaysia - Mahayana, Maman S. (UI Scholars Hub, 2007)
For a long period, the Indonesian and Malaysia relationship has proved the single root of socio-cultural tradition. Yet, the London Treaty 1824, an agreement between the British and Dutch colonials, failed to split the emotional bond between the two nations. Although this treaty successfully divided the Malay Kingdom into two different political region, where Singapore (Temasek) and Johor was politically put under British rule while Riau and Lingga was put under the Dutch, the socio-cultural communication among the people in those areas remained undisturbed by the political decision of the two colonial rulers. Even, during the Indonesia-Malaysia confrontation period, the people were persistently busy keeping their own business in the social, cultural and trade affairs. Hence, specifically since the day prior to their independence, the cultural movement is considerably significant for the people in this region.